2023
DOI: 10.1371/journal.pmed.1004186
|View full text |Cite|
|
Sign up to set email alerts
|

Fortified balanced energy–protein supplementation during pregnancy and lactation and infant growth in rural Burkina Faso: A 2 × 2 factorial individually randomized controlled trial

Abstract: Background Optimal nutrition is crucial during the critical period of the first 1,000 days from conception to 2 years after birth. Prenatal and postnatal supplementation of mothers with multimicronutrient-fortified balanced energy–protein (BEP) supplements is a potential nutritional intervention. However, evidence on the long-term effects of BEP supplementation on child growth is inconsistent. We evaluated the efficacy of daily fortified BEP supplementation during pregnancy and lactation on infant growth in ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…The observed effects of prenatal BEP on newborn FFMI can be seen in relation to the subsequent modest effect of prenatal BEP on linear growth achieved at 6 months of age (0.11 z-score; 95% CI: 0.01, 0.21; p = 0.032) that we reported previously [ 52 ]. In Ethiopia, Admassu and colleagues [ 53 ] found that newborn FFM, but not FM, was positively associated with height-for-age z-score at 2 years of age.…”
Section: Discussionsupporting
confidence: 67%
“…The observed effects of prenatal BEP on newborn FFMI can be seen in relation to the subsequent modest effect of prenatal BEP on linear growth achieved at 6 months of age (0.11 z-score; 95% CI: 0.01, 0.21; p = 0.032) that we reported previously [ 52 ]. In Ethiopia, Admassu and colleagues [ 53 ] found that newborn FFM, but not FM, was positively associated with height-for-age z-score at 2 years of age.…”
Section: Discussionsupporting
confidence: 67%
“…The primary outcomes were the prevalence of SGA at birth (<10th percentile of the newborns size standards of the International Fetal and Newborn Growth Consortium for the 21st Century (INTERGROWTH-21st) [ 9 ] (Villar et al, 2013)) and the length-for-age z-score (LAZ) at 6 months of age (calculated using the WHO’s 2006 growth reference at 6 months of age [ 10 ] (de Onis and Branca, 2016)). These results have been published [ 11 , 12 , 13 ] (de Kok et al, 2022; Argaw, de Kok, et al, 2023; Argaw, Toe, et al, 2023).…”
Section: Introductionsupporting
confidence: 70%
“…However, iron and folic acid supplementation in the form of BEP or IFA tablets formulations did not improve anemia prevalence during pregnancy (60). Similarly, there was a high prevalence of infant anemia at 6 months of age in both intervention and control groups (61) suggesting the limited effect of maternal iron and folic acid supplementations in the form of BEP and IFA tablets formulations. On the other hand, the exploratory analysis here indicated a beneficial role of BEP in mitigating the negative effect of OTA exposure on increased infant anemia at the age of 6 months.…”
Section: Discussionmentioning
confidence: 99%